The EFFECT OF GIVING SOYBEAN MILK ON REDUCTION OF HOT FLUSH SYMPTOMS IN CLIMACTERIUM WOMEN - Kianti Nurfadilah (JURNAL KEBIDANAN, 2022)
Background: Hot flush during the climacteric period affects the quality of life of a mother. Hot flushes are caused by a decrease in the hormone estrogen which results in symptoms such as night sweats, palpitations and feelings of uncertainty. If not treated it will worsen the condition of the mother climacterium. Soy milk can reduce symptoms hot flush in climacteric mothers. Objective: This study aims to determine the effect of giving soy milk to the reduction of symptoms hot flush in PMB N Karawang, West Java in the treatment group and the control group. Methodology: This study uses a quasi-experimental research design (quasy experimental) using aapproach pre-experimental design of one group pretest-posttest type posttest (initial test andin a single group). The sample of this study amounted to 14 climacteric mothers. This sample uses incidental sampling with data collection based on inclusion criteria.. The research instrument consisted of the Daily Diary of Hot Flashes (DDHF), soy milk, observation sheets and informed consent. The data were analyzed using the test Wilcoxon to determine whether there was a difference in giving soy milk to climacteric mothers. Research Results: The results showed that there was a significant difference in scores before and after being given soy milk (p<0.05).